Dynamic business law - Nancy K. Kubasek
Emphasis on the BUSINESS in business law. Dynamic Business Law emphasizes the tie of legal issues back to the core business curriculum. This will help both students and faculty. Faculty need to know how this is integrated as they are constantly defending' the inclusion of this course in the business curriculum. And students need to understand how the concepts tie to their future business careers